Predictive value of the angiogenic test (sFlt / PIGF ratio) in hypertensive disorders of pregnancy. Perinatal results in Cienfuegos - Vivian Rosa Vázquez Martínez; Cristóbal Jorge Torres González; Greter Torres Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Background: Preeclampsia is the main cause of morbidity, mortality, maternal and perinatal disability, making its diagnosis and prevention important. Objective: to validate the predictive value of the angiogenic test (sFlt / PIGF ratio) in hypertensive disorders of pregnancy. Methods: a descriptive cross-sectional study was carried out at the Gynecology and Obstetrics Service, Dr. Gustavo Aldereguía Lima Hospital, Cienfuegos, from January 2017 to December 2018. 125 pregnant women with suspected pre-eclampsia, from the Total number of patients admitted with high blood pressure were studied. They were divided into two groups according to the diagnostic values of the Roche angiogenic test (sFlt / PIGF ratio), and perinatal results and maternal complications were compared. The Chi square statistic (p <0.05) was used and the risk ratio (95% CI) was calculated. Results: the angiogenic test was positive more frequently in those pregnant women who developed eclampsia preeclamsia, with 90.7% vs. 9.3% in those who did not develop eclampsia preeclamsia (p = 0.000); as well as those less than 34 weeks of gestational age who developed pre-eclampsia (72%), with high sensitivity and specificity. The use of the test in the follow-up of the patients was associated with a tendency to prolong the pregnancy. Its positivity was more related to maternal, fetal and neonatal complications. Conclusion: a positive value of the test implies an increased risk of developing preeclamsia eclampsia and maternal complications, as well as adverse perinatal results. The angiogenic test showed utility in the diagnosis and prognosis of the disease.